2016
DOI: 10.1111/neup.12291
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological features of pituicytoma and the differential diagnosis of sellar glioma

Abstract: Pituicytoma is rare and difficult to diagnose. This study explored the clinicopathological features, immunophenotype and differential diagnosis of pituicytoma. We compared 11 cases of pituicytoma and 26 cases of sellar glioma (16 pilocytic astrocytomas, four diffuse astrocytomas, three pilomyxoid astrocytomas, and three third ventricle chordoid gliomas). The 11 pituicytoma cases involved six men and five women (age: 33-65 years). Three of the 11 patients experienced recurrence due to a residual tumor, and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 27 publications
5
44
0
3
Order By: Relevance
“…We observed tissue fragments in all cases and note that the tumor cells often were closely associated with vessels. This finding mirrors what has been reported histologically; specifically that pituicytomas may show cells radiating around vessels and even have some morphologic overlap with ependymomas . Our findings are consistent with what has been previously described for pituicytomas and expands on the range of features that may be seen.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We observed tissue fragments in all cases and note that the tumor cells often were closely associated with vessels. This finding mirrors what has been reported histologically; specifically that pituicytomas may show cells radiating around vessels and even have some morphologic overlap with ependymomas . Our findings are consistent with what has been previously described for pituicytomas and expands on the range of features that may be seen.…”
Section: Discussionmentioning
confidence: 97%
“…The radiologic findings of pituicytomas are nonspecific and studies have found that pituicytomas are nearly always misdiagnosed prior to surgery, likely due to their radiographic overlap with other tumors of the sellar region including pituitary adenomas, craniopharyngiomas, and meningiomas . Similar to the radiographic features, the morphologies of pituicytomas also show overlap with other tumors commonly found in the sellar/suprasellar region.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Pituicytoma is supposed to derive from the neoplastic transformation of pituicytes, which are specialized glial cells of neurohypophysis . It is histologically composed of elongated bipolar spindle cells arranged in fascicles or in a storiform pattern and it has peculiar a immunohistochemical profile, with positive staining for vimentin, S100 and TTF‐1, variable (patchy to diffuse) staining for GFAP and EMA and absence of staining for cytokeratins, synaptophysin, chromogranin and pituitary hormones …”
Section: Discussionmentioning
confidence: 99%